HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP KEPATUHAN DALAM MENGKONSUMSI TABLET Fe DI WILAYAH KERJA PUSKESMAS LAMPAHAN TAHUN 2023 - Farni, Siska; Arami, Nova; HS, Nurlaely (Jurnal Ilmiah Cerebral Medika, 2024)
ABSTRACTThe maternal mortality rate (MMR) is an indicator to see the degree of women's welfare and the targets set in development goals. The causes of the high MMR in Indonesia are maternal deaths with bleeding (25%), sepsis (15%),This type of research is analytic in nature, using a correlational method with an approach designcross sectional. The sampling technique used methodaccidental sampling is a portion of the population, namely 35 pregnant women. Processing and analysis of data usingwho squares.The results showed that the majority were still found to have less knowledge, 19 people (54.3%) and those with good knowledge, 10 people (28.6%), while those who had good knowledge, 6 people (17.1%). The majority of respondents had a negative attitude in consuming iron (Fe) tablets, namely 20 people (57.1%). On testwho squaresshows the knowledge variable can be seen by valueP value of 0.01 (P< 0,05) and attitude variable with valueP value of 0.00 (P< 0,00). So it can be concluded that there is a relationship between knowledge and attitudes with adherence to consumption of iron (Fe) tablets.Keywords : Compliance with consumption of iron tablets, knowledge, attitude